On temporal partitioning of a community of ectomycorrhizal fungi - Koide, Roger T.; Shumway, Durland L.; Xu, Bing; Sharda, Jori N. (The New phytologist, 2007)
Several mechanisms may contribute to the high species richness often reported in ectomycorrhizal (ECM) fungal communities, including spatial and temporal partitioning. Here, we focus on temporal partitioning. Using molecular methods, we determined the frequencies of occurrence of ECM fungal species detected as hyphae and ECM roots in the forest floor of a Pinus resinosa plantation during a 13-month period. We then used a novel statistical procedure to place the most frequently occurring ECM fungal species into groups distinguished by their patterns of relative frequency over time. Three groups with contrasting temporal patterns were distinguishable for fungal species detected as hyphae. Two groups were distinguishable for species detected as ECM roots. Our results support the hypothesis that temporal partitioning occurs among the species of ECM fungi in this community, but we did not address its causes, which may have involved interactions among species' physiological tolerances, temporal environmental variability, temporal patterns of root production, and variation in fungal genet lifespan. These interactions should be the subjects of future research.